The context of nursing – HIV+ client professional relation: rights and duties - Juliana Fechine Braz de Oliveira; Inacia Sátiro Xavier de França (Rev Rene)
This study aimed at verifying: prejudice faced by HIV+ clients and information they have concerning their rights and duties; position of nursing professionals on their rights and duties when treating a HIV+ patient. HIV+ clients assisted by the Group of Life Support (GLS) and the nursing team of an infectology ambulatory participated in the study. Most HIV+patients are aware of their rights and duties but they do not fight for them. There is prejudice and disrespect by some nursing professionals. Nevertheless, most of them know and respect the right of clients.